Por trás da cena: as relações entre televisão e espetáculos teatrais - Figueiredo, Beatriz Helena Ramsthaler (2015)
Over the past two decades in Brazil (1991-2012), the scenario involving the relationship between television and theatrical performances comprises the intertwining of media with public cultural policies, specifically in view of the enforcement of the Rouanet Law (Federal Law for the Promotion of Culture) . Theatrical performances of various natures are mediated by a publicity relationship with television. Many are structured considering the actor of national recognition (often produced by the media structures), both for funding and for ensuring the dissemination or accession of the audience. The media takes over the cultural duties and assigns them values that should be brought to light to be discussed by the social agents who think, use, produce and create the mechanisms that support culture in the country. The question guiding this research is that an economy based on tax incentive socially builds certain symbolic values for culture, in an operation that ends up regulating the survival of this artistic segment due to the type of social significance that it promotes. The hypothesis is that the media standardize the expansion of certain types of theater, and the Brazilian broadcast television has a specific role, which produces a market trait that impacts the theatrical production in the country. In this sense, the media has acted similarly to the parameter of natural selection in the evolution process explained by Charles Darwin, in 1859. To explore this hypothesis, we adopted the Bodymedia Theory (Katz & Greiner), which pleads a relationship of codependence between body and environment, which in this study will be transformed into the structural axis of the literature on television (Arlindo Machado and Elizabeth Bastos Duarte), media (Siegfried Zielinsky and Armand Mattelart), cultural policies (Leonardo Brant, Antonio Albino Canelas Rubim and Lia Calabre) and culture (Amálio Pinheiro, Néstor Garcia Canclini, Boaventura de Sousa Santos and Serge Gruzinsky). The methodology is that of the literature review to make it possible to build a critical reading of the culture-communication relationship that is expressed in some case studies, in a way that cultural diversity is maintained and respected in a country that stands out for this characteristic